2021
DOI: 10.1007/978-3-030-82014-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Modeling as a Means of Solving Professionally-Oriented Problems in Maritime Industry

Abstract: Simulation modeling is one of the most commonly used methods of studying the functioning of complex systems to assess possible risks. The use of simulation methods allows us not only to conduct a detailed analysis of the situation, but also to assess the probability of avoiding or appearance of a threat. The ship's crew must be staffed by qualified seafarers who have received a favorable decision from the management of crewing companies. Such commissions assess the applicant's competence at the international l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Prokhorov, V. Frolov, H. Kravtsov [14] the algorithm for carrying out the expertise was developed. The authors of the research [15] have used the algorithm developed several times in previous research and it showed positive results. The group of experts who are qualified professional in maritime engineering have studied the functions of the suggested computer-based model and assessed its occupational potential.…”
Section: Research Resultsmentioning
confidence: 99%
“…Prokhorov, V. Frolov, H. Kravtsov [14] the algorithm for carrying out the expertise was developed. The authors of the research [15] have used the algorithm developed several times in previous research and it showed positive results. The group of experts who are qualified professional in maritime engineering have studied the functions of the suggested computer-based model and assessed its occupational potential.…”
Section: Research Resultsmentioning
confidence: 99%
“…The subject matter experts stress out that the risks of shipboard emergencies arise from the inaccurate or untimely information and they believe that to solve this problem it is necessary to use the scientific approach which will provide for the well-reasoned technology for the information provision research in the vessel traffic control systems. The complex use of modern information technologies on ships is described in the publications of Voloshynov et al [34], Zaytseva et al [35].…”
Section: Related Workmentioning
confidence: 99%